The ‘new normal’ in higher education: innovative teaching and learning technologies and practices during a crisis - Mavengere, Nicholas Blessing; Pondiwa, Shepard; Matiyenga, Tinashe Charles; Manzira, Francis; Mutanga, Alfred (2022)
Purpose The purpose of this paper is to analyze the effectiveness of innovative technologies and practices adopted to enhance teaching and learning in higher education settings during a crisis e.g. the COVID-19 pandemic in developing countries. We seek to highlight the need for digital and technological transformation in the teaching and learning practices in response to crisis for adaptation to the ‘new normal’. Design /Methodology approach Using a qualitative research approach, data was collected through an online questionnaire and online interviews with lecturers who conducted teaching during the COVID-19 pandemic in developing countries. The countries from where data was collected are Egypt, Zimbabwe, South Africa, Tanzania, Namibia and Botswana. The aim was to highlight transformational processes required for to remote learning during the COVID-19 pandemic. In doing so, we note the adaptable approaches that are useful in times of crisis to promote learning. Findings, contributions and implications The results highlight measures adopted to promote remote learning during a crisis, such as, COVID-19. The contributions include a conceptual model for innovative technologies and practices to the rapid shift to remote learning and ensuring qualities of learning. In developing countries’ context, making use of existing infrastructure, system and organizations is necessary to promote learning in higher education.